2012
DOI: 10.1159/000338906
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hyponatremia in Acute Stroke Stage with Three-Year Mortality in Patients with First-Ever Ischemic Stroke

Abstract: Background: Hyponatremia is the most common electrolyte disorder in hospitalized patients, and is frequently a marker of a significant underlying disease. The prognostic value of hyponatremia in patients with acute first-ever ischemic stroke is not known. We aimed to analyze whether hyponatremia in the acute stroke stage contributed to the risk of mortality or recurrent stroke in these patients. Methods: We studied 925 patients presenting with acute first-ever ischemic stroke between 2002 and 2004. Sodium leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 43 publications
4
53
1
2
Order By: Relevance
“…Hyponatremia, a common electrolyte disturbance, is associated with poor prognosis in patients with acute heart failure [1,2], liver cirrhosis [3], CKD [4,5], and stroke [17,18]. The prognostic value of serum sodium levels in patients with coronary artery disease has also been previously evaluated; however, the results obtained were conflicting [6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Hyponatremia, a common electrolyte disturbance, is associated with poor prognosis in patients with acute heart failure [1,2], liver cirrhosis [3], CKD [4,5], and stroke [17,18]. The prognostic value of serum sodium levels in patients with coronary artery disease has also been previously evaluated; however, the results obtained were conflicting [6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…At the clinical level, a meta-analysis showed that fever is associated with morbidity and mortality after stroke [42]. Electrolyte imbalance, especially hyponatremia, may worsen cerebral edema [43] and hyponatremic stroke patients may have an increased long-term mortality [44]. The entry of bacteria and lipopolysaccharide into the blood stream activates the coagulation as well as fibrinolysis systems and may theoretically result in the extension of the infarcted area [45].…”
Section: The Pathophysiology Of Potential Stroke Worsening As a Resulmentioning
confidence: 99%
“…Hyponatremia is a consistent predictor of adverse outcomes not only in general medical and critically ill patients (11)(12)(13)(14) but also in those with acute ischemic stroke (15,16). A possible explanatory mechanism for the association in patients with stroke is fluid shift in intracranial tissue leading to cerebral edema, seizures, and delayed cerebral ischemia (17).…”
mentioning
confidence: 99%